Kinetics of Oxidation of Rosaniline Hydrochloride by Potassium Peroxydisulphate in Mixed Micelles of Binary Surfactant System - M. Joshi, Hitendra; Nagar, T.N. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of rosaniline hydrochloride (R–HCl) has been studied in binary combinations of cationic/nonionic and anionic/nonionic surfactant systems at 30ºC. The pre-micellar environment of single C16TABr catalyses the reactions whereas single sodium dodecyl sulphate (SDS) and nonionic surfactants, viz., Triton X-100, Triton X-102, Tween-20 lind Tween-80 strongly inhibit the reaction rate of R–HCl. The values of rate constant in mixed micellar solutions (C16TABr + Tween-20, C16TABr + Tween-80) are less than the single cationic surfactant but are higher than the single nonionic surfactant; while the value of rate constant in mixed micellar solutions (SDS + Triton X-100, SDS + Triton X-102) is less than that in single anionic as well as in nonionic surfactant.